2021
DOI: 10.4314/ahs.v21i1.49
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of asphyxia neonatorum among live births at Debre Tabor General Hospital, North Central Ethiopia: a cross-sectional study

Abstract: Background: More than one third of the neonatal deaths at Neonatal Intensive Care Unit of Debre Tabor General Hos- pital (DTGH) are attributable to birth asphyxia. Most of these neonates are referred from maternity ward of the hospital. However, there is no recent evidence on the prevalence and specific determinants of birth asphyxia at DTGH. Besides, public health importance of factors like birth spacing weren’t addressed in the prior studies. Methods: A cross sectional study was conducted on a sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(55 reference statements)
0
4
0
3
Order By: Relevance
“…A newborn was considered to have neonatal asphyxia when its fifth minute APGAR score was less than seven [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…A newborn was considered to have neonatal asphyxia when its fifth minute APGAR score was less than seven [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…29 While this rate is higher than the 1.9% reported from a study in Ghana, and some studies in Ethiopia that reported rates ranging from 6.7% to 13.8%,it is lower than 17.8%, 18.1%, 27.1%, and 32% reported from other studies also done in Ethiopia. 26,9,[18][19][20][21][22][23][24] Reported rates of low fifth minute Apgar score are much lower outside Africa. It was 0.46% in a study done in Brazil, 0.57% in a study in Peru and 1.2% in a study in the USA.…”
Section: Rate Of Low Fifth Minute Apgar Scorementioning
confidence: 99%
“…15,41 Several studies have documented independent fetal/neonatal and maternal factors associated with low fifth minute Apgar score. 9,[16][17][18][19][20][21][22][23][24][26][27][28][42][43][44][45][46] No previous study has been undertaken at the Federal Medical Centre Yenagoa, Bayelsa State, Nigeria, to assess the rate of low fifth minute Apgar score and its determinants, hence the need for this study to add to the data and knowledge from south-south Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura aponta que a asfixia perinatal apresenta múltiplos fatores de risco, incluindo trabalho de parto prolongado, ruptura prematura de membrana, local de parto, complicações obstétricas pré-natais, paridade, nascimentos múltiplos, idade gestacional (IG) menor que 37 semanas ou maior que 41 semanas, baixo peso ao nascer, apresentação fetal não cefálica e sofrimento fetal agudo (Sendeku et al, 2020;Bayih et al, 2021;Kune et al, 2021;Tegegnework et al, 2022;Getaneh et al, 2022).…”
Section: • Introduçãounclassified